Segregation Toward Black Americans as Consequence of Racism in To Kill a Mockingbird by Harper Lee - Eriska Tyas Yustisia; Yosep Bambang Margono (Universitas 17 Agustus 1945 Semarang, 2022)
This paper, entitled Segregation Toward Black Americans as Consequence of Racism in To Kill a Mockingbird by Harper Lee discusses racism that reflected in the novel, focusing on the segregation for Black people. At the beginning Black people is an enslaved person for White people. Racism sees that the reality and entity of a person based on the anatomical factors from a particular ethnic. Racism does not value someone based on the intellectual matters. Racism defines, values, and views people only based on the racial affiliation. Racism can cause negative impacts for the victim who receives the treatment. The treatment of racism also can be affecting the psychology of the victim. Racism in the United States of America cause many negative sides. One of the negative sides is segregation. The White people believe that segregation is the correct way to live with Black people. From the slavery it become segregation. To analyse this novel, the writer using Abrams’ mimetic theory. Mimetic theory is the most ancient theory of all. Mimetic came from the word mimesis in the Ancient Greek term. The meaning of mimesis is imitation or representation. The result of the analysis, shows there are three levels of racism, structural racism, personally mediated racism, and internalized racism, also segregation toward Black people. Keywords: Racism, segregation, Black people, To Kill a Mockingbird, mimetic theory.